2014
DOI: 10.1002/hed.23400
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment circulating monocyte count associated with poor prognosis in patients with oral cavity cancer

Abstract: A higher pretreatment circulating monocyte count can be considered as a useful prognostic marker in patients with oral cavity cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
112
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 46 publications
7
112
0
Order By: Relevance
“…They also reported that NLR might be a promising serum biomarker for diagnosis and prognostication of PTC (Seretis et al, 2013). In another study, Tsai et al reported an increase in NLR in parallel with the advancement of clinical stage in the patients with oral cavity cancer, and in contrast, a reduction in the lymphocyte count (Tsai et al, 2013). Similarly, pretreatment NLR was found as a strong prognostic factor in nasopharyngeal carcinoma patients .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They also reported that NLR might be a promising serum biomarker for diagnosis and prognostication of PTC (Seretis et al, 2013). In another study, Tsai et al reported an increase in NLR in parallel with the advancement of clinical stage in the patients with oral cavity cancer, and in contrast, a reduction in the lymphocyte count (Tsai et al, 2013). Similarly, pretreatment NLR was found as a strong prognostic factor in nasopharyngeal carcinoma patients .…”
Section: Discussionmentioning
confidence: 93%
“…The presence of an elevated preoperative NLR has been validated as a marker of inflammation, and shown to have prognostic significance for a number of tumors (Jung et al, 2011;Idowu et al, 2012;Liu et al, 2013;Unal et al, 2013), including HNSCC (Trellakis et al, 2011;Millrud et al, 2012;Perisanidis et al, 2013;Rassouli et al, 2013;Tsai et al, 2013). It is considered as a marker of systemic inflammation which may predict worse prognosis by driving cancer cell proliferation through increasing the availability of growth factors, angiogenic factors and other pro-neoplastic signaling molecules (Hanahan and Weinberg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophilia may be a marker of inflammation-related aggressive biological behaviour of the tumor (18). Absolute neutrophil and lymphocyte counts may be affected by various physiological, pathological and physical factors, although NLR may remain stable with respect to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophilia may inhibit the immune system by suppressing lymphocytes, activated T cells and natural killer cells (3,17). The prognostic role of the NLR has been evaluated in >60 studies on a number of solid tumors (7)(8)(9)(10)(11)(12)(13)(14)16,18).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the work of Tsai et al, who reported that pretreatment total WBCs count, NC, LC and NLR were not significantly associated with cancer-specific survival in oral cancer patients. Instead, the authors found that pretreatment monocytes count had a significant association with survival in these patients (12) .…”
Section: Discussion:-mentioning
confidence: 93%